POTENSI CENDAWAN ENDOFIT DALAM MENGENDALIKAN Fusarium oxysporum f.sp. cubense DAN NEMATODA Radopholus similis Cobb. PADA TANAMAN PISANG BARANGAN (Musa paradisiaca L.) DI RUMAH KACA - Rizki Trianno Sinaga; Lisnawita Lisnawita (Jurnal Agroekoteknologi, 2013)
Potential of endophytic fungal to control Fusarium oxysporum f.sp. cubense (Foc) andnematode Radopholus similis (Rs) on banana cv. Barangan (Musa paradisiaca L.) crop ongreenhouse. This research aims to intens and find potential endophytic as biocontrol agents tocontrol Foc and Rs on banana cv. Barangan crop. This research used Completely RandomizedDesign (CRD) non factorial consist thrithteen treatments and three replications. Replications;control (without inoculated), inoculated 300 Rs, inoculated Foc, inoculated 300 Rs one week laterinoculated Foc two weeks later inoculated endophytic 5BSBH’s isolate, inoculated 300 Rs oneweek later inoculated Foc two weeks later inoculated endophytic 4BSU’s isolate, inoculated 300 Rsone week later inoculated Foc two weeks later inoculated endophytic 1BJH’s isolate, inoculated 300Rs one week later inoculated Foc two weeks later inoculated endophytic 1BTAH’s isolate,inoculated 300 Rs one week later inoculated Foc two weeks later inoculated endophytic 1BSHT’sisolate, inoculated endophytic 5BSBH’s isolate one week later inoculated 300 Rs two weeks laterinoculated Foc, inoculated endophytic 4BSU’s isolate one week later inoculated 300 Rs two weekslater inoculated Foc, inoculated endophytic 1BJH’s isolate one week later inoculated 300 Rs twoweeks later inoculated Foc, inoculated endophytic 5BSBH’s isolate one week later inoculated 300Rs two weeks later inoculated Foc, inoculated endophytic 1BSHT’s isolate one week laterinoculated 300 Rs two weeks later inoculated Foc. The results showed that endophytic fungal hadthe potency as biocontrol agent in controlling Fusarium wilt of banana cv. Barangan.Keywords: Endophytic fungal, Fusarium oxysporum f.sp. cubense, Radopholus similis.